Assessment of animal diseases caused by bacteria resistant to antimicrobials: Dogs and cats. (28th June 2021) - ,; Nielsen, Søren Saxmose; Bicout, Dominique Joseph; Calistri, Paolo; Canali, Elisabetta; Drewe, Julian Ashley; Garin‐Bastuji, Bruno; Gonzales Rojas, Jose Luis; Gortazar Schmidt, Christian; Herskin, Mette; Michel, Virginie; Miranda Chueca, Miguel Angel; et al.
Abstract: In this opinion the antimicrobial‐resistant bacteria responsible for transmissible diseases that constitute a threat to dog and cat health have been assessed. The assessment has been performed following a methodology based on information collected via an extensive literature review and expert judgement. Details of the methodology used for this assessment are explained in a separate opinion. A global state of play of antimicrobial resistant Staphylococcus pseudintermedius, Staphylococcus aureus, Staphylococcus schleiferi, Escherichia coli, Proteus mirabilis, Klebsiella spp., Enterobacter spp., Pseudomonas aeruginosa, Clostridium perfringens, Clostridioides difficile, Enterococcus faecalis and Enterococcus faecium has been provided. Among those bacteria, EFSA identified S. pseudintermedius, E. coli and P. aeruginosa with > 90% certainty as the most relevant antimicrobial resistant bacteria in the EU based on the available evidence. The animal health impact of these most relevant bacteria, as well as their eligibility for being listed and categorised within the animal health law framework will be assessed in separate scientific opinions.